2005
DOI: 10.1002/jgm.741
|View full text |Cite
|
Sign up to set email alerts
|

Poor intercellular transport and absence of enhanced antiproliferative activity after non‐viral gene transfer of VP22‐P53 or P53‐VP22 fusions into p53 null cell lines in vitro or in vivo

Abstract: Our study indicates that a gene transfer strategy using VP22 cannot be considered as a universal system to improve the delivery of any protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
5

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 38 publications
(63 reference statements)
0
5
0
5
Order By: Relevance
“…However, the transfection efficiency is still low (o1% of the tumor cells), but we previously demonstrated that it is sufficient to successfully deliver p53-, bax-or p27-encoding plasmids. [26][27][28] In this study, we show that despite this very low transfection efficiency, a significant reduction of tumor growth can be observed after direct intratumoral injection of HERV-W-or GALV-, but not RD-FMG-encoding plasmids. This strong antitumor response suggests that FMG genes and especially HERV-W and GALV are very potent and promising tools for the treatment of human lung tumors, especially in immunecompetent animals where we know that this direct cell-killing activity of FMG will also be supported by release of highly immunogenic exosome-like vesicles.…”
Section: Fmg-mediated Tumor Therapy E-h Lin Et Almentioning
confidence: 63%
See 1 more Smart Citation
“…However, the transfection efficiency is still low (o1% of the tumor cells), but we previously demonstrated that it is sufficient to successfully deliver p53-, bax-or p27-encoding plasmids. [26][27][28] In this study, we show that despite this very low transfection efficiency, a significant reduction of tumor growth can be observed after direct intratumoral injection of HERV-W-or GALV-, but not RD-FMG-encoding plasmids. This strong antitumor response suggests that FMG genes and especially HERV-W and GALV are very potent and promising tools for the treatment of human lung tumors, especially in immunecompetent animals where we know that this direct cell-killing activity of FMG will also be supported by release of highly immunogenic exosome-like vesicles.…”
Section: Fmg-mediated Tumor Therapy E-h Lin Et Almentioning
confidence: 63%
“…29 Fusion proteins between VP22 and a therapeutic polypeptide were thus successfully used for in vivo tumor therapy although conflicting results have also been reported. 27,28,[30][31][32][33][34][35] Positive gene therapy results using suicide genes like the herpes simplex type-1 thymidine …”
Section: Discussionmentioning
confidence: 99%
“…The transport of chimeric proteins consisting of VP22 covalently bound to green fluorescent protein (GFP) or other proteins from cell to cell has been disputed (1,2,4,10,17,20,22,28,33,38,55,58,59). The conflicting reports remain to be resolved, but it should be pointed out that some proteins are readily extracted during methanol fixation of cells and that covalently bound polypeptides of a size nearly equivalent to or larger than VP22 could be expected to change the properties of the protein.…”
mentioning
confidence: 99%
“…La proteína p53 tiene un peso molecular de 53 kD (de ahí su nombre) y su principal característica es que interviene directamente en el control del ciclo celular y en la replicación y reparación del ácido desoxirribonucleico (ADN), manteniendo la estabilidad genómica, activando la apoptosis y participando en la respuesta celular a agentes externos nocivos. La proteína p53 es fundamentalmente un regulador de la expresión génica, actuando como factor de transcripción capaz de activar o de inhibir genes específicos, entre los que destacan el gen p21, los genes bax y fas, el gen IGF-BP3 (insulin-like growth factor-binding protein-3), el gen gadd45 (growth arrest and DNA damage-45) y el gen de la ciclina G, todos ellos implicados en el ciclo de división celular y por ende en los procesos de proliferación y apoptosis (1,2). De estas mismas funciones deriva el hecho de que la proteína supresora de tumores p53 está relacionada con la prevención de cáncer, debido a su habilidad para regular la transformación, proliferación y muerte celular ante diversos agentes, entre ellos la agresión a los ácidos nucleicos y el estrés oncogénico (1)(2)(3)(4).…”
Section: Introductionunclassified
“…La proteína p53 es fundamentalmente un regulador de la expresión génica, actuando como factor de transcripción capaz de activar o de inhibir genes específicos, entre los que destacan el gen p21, los genes bax y fas, el gen IGF-BP3 (insulin-like growth factor-binding protein-3), el gen gadd45 (growth arrest and DNA damage-45) y el gen de la ciclina G, todos ellos implicados en el ciclo de división celular y por ende en los procesos de proliferación y apoptosis (1,2). De estas mismas funciones deriva el hecho de que la proteína supresora de tumores p53 está relacionada con la prevención de cáncer, debido a su habilidad para regular la transformación, proliferación y muerte celular ante diversos agentes, entre ellos la agresión a los ácidos nucleicos y el estrés oncogénico (1)(2)(3)(4). El gen p53 codifica la proteína p53 y en el genoma humano parecen existir unas 200 copias de este gen, localizadas en el cromosoma 17.…”
Section: Introductionunclassified